IMPLEMENTASI REMOTE AUDIT DI ERA PANDEMI COVID-19 - AWISIANTI, MITA; Susilo, Ghina Fitri Ariesta (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The COVID-19 pandemic has caused the structure of life to change, such as the way auditors work. All access is limited and the auditor's work is hampered. So one alternative that can be done is to carry out a remote audit. This study aims to determine the implementation of remote audits in the era of the COVID-19 pandemic. This study uses a qualitative approach and is included in the literature review. The data used by researchers is secondary data, namely using previous research. Sources of information are obtained by collecting relevant information regarding the implementation of remote audits in the era of the COVID-19 pandemic. The results of the study show that the implementation of remote audits has been carried out by foreign government entities and by domestic agencies or institutions. The remote audit implementation includes the planning stages, document review, field inspections, remote interviews and closing meetings.